Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities